Populist economic policy in the postwar period: 1945-1948 - García, Mirella (1986)
This paper tries to rebuild the socio political and economic scenario at the time of the economic populist policy of the Bustamante-APRA administration. The purpose of this paper is to demonstrate that the two political parties on 1945 achieved power on a non-solid basis which would not let the parties understand each other in order to implement the policies of the populist and the national project. Furthermore, it intends to demonstrate that the industrial groups were not pushed forward by the government toward a clear pro-industrial policy which made them support the original coalition or made them re-structure a new alliance with Bustamante and the infernal progressist forces. It also tries to make a balance in order to find out about the populist measures which led to the political and economic crisis. Finally, it wants to emphasize the exporters' deliberate attitude of sabotaging the government's measures since the final growth in '45 was obtained at the expense of this economic sector.